PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DI TOSERBA YOGYA MAJENANG (Studi Kasus pada Konsumen Toserba Yogya Majenang) - Supriyanto; Esih Jayanti; Zamroni (JURNAL EKONOMI, 2023)
This study aims to determine the effect of service quality, product quality, and price on purchasing decisions at the Yogya Majenang Department Store. The method used in this study using quantitative methods with the sample used in this study as many as 100 people. The analysis techniques used include validity test, reliability test, MSI (Method Succesive Interval), and classical assumption test which includes normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis test, and statistical test which includes T test, F test and test the analysis of the coefficient of determination (R2).Based on the results of the analysis obtained that service quality has no significant effect on purchasing decisions, this is indicated by the tcount value of service quality of 0.656 < ttable 1.985 or in other words H1 is rejected and H0 is accepted, while product quality has a significant effect on purchasing decisions with a tcount value of product quality. of 6.432 > ttable 1.985 or in other words H2 is accepted and H0 is rejected, and the price also has a significant effect on purchasing decisions with a t-value of 10,442 > ttable 1.985 in other words stating that H3 is accepted and H0 is rejected. In testing the four variables simultaneously service quality, product quality and price have a significant effect on purchasing decisions. This is indicated by the value of the F test which produces an fcount value of 132.870 > ftable 3.09 in other words stating that H4 is accepted and H0 is rejected.